Analisis Perencanaan Pembangunan Desa Di Desa Sukamaju Kecamatan Cilawu Kabupaten Garut - Gugun Geusan Akbar; Yusuf Hermawan; Ai Lina Karlina (Jurnal Pembangunan dan Kebijakan Publik (JPKP), 2019)
The background of this research is the phenomenon of village development planning in Sukamaju village which has not been implemented well due to the low human resources in knowledge about RKPDes. The planning of the development in Sukamaju Village using the theory of Syaodih consists of achieving better goals in the future, utilizing resources optimally, paying attention to limitations and striving for efficiency and effectiveness. The purpose of this study is to know the Village Government Working Plan in Sukamaju Village Cilawu District Garut Regency in 2018. This research uses descriptive analysis method. The author took the research location in Sukamaju Village Cilawu District Garut Regency, involving Sukamaju Village government and community Sukamaju Village District Cilawu Garut regency with the number of informants 5 people. From the interviews and observations, it is found that RKPDes in Sukamaju village is still lacking in human resources aspect because the team in RKPDes is still new and not yet understand its duty and its function to run RKPDes. But the effort from Sukamaju Village is to conduct guidance and counseling for Sukamaju Village employees.